2020
DOI: 10.7557/14.4703
|View full text |Cite
|
Sign up to set email alerts
|

Kan omvendt undervisning gi bedre læringsutbytte i legemiddelregning, sammenlignet med tradisjonell undervisning? En kvasieksperimentell kontrollert studie

Abstract: Flipped classroom improves student learning in dosage calculation, - a quasi-experimental control group design The flipped classroom method has received increased attention in health sciences education, however, few studies have investigated performance data showing its effectiveness. The aim of this study was to compare learning outcome in a flipped classroom with a standard lecture. The hypothesis was that applying a flipped classroom model in a dosage calculation class would improve learning outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Students can also find that a flipped classroom approach is a pleasant experience, compared to a traditional lecture [94]. Flipped classrooms are recommended for use on health subjects [95,96]. In a Norwegian quasi-experimental study, a flipped classroom was found to lower the failure rate in dosage calculation exams with 22 percentage points [96].…”
Section: Pedagogical Strategies Related To Pathology Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Students can also find that a flipped classroom approach is a pleasant experience, compared to a traditional lecture [94]. Flipped classrooms are recommended for use on health subjects [95,96]. In a Norwegian quasi-experimental study, a flipped classroom was found to lower the failure rate in dosage calculation exams with 22 percentage points [96].…”
Section: Pedagogical Strategies Related To Pathology Teachingmentioning
confidence: 99%
“…Flipped classrooms are recommended for use on health subjects [95,96]. In a Norwegian quasi-experimental study, a flipped classroom was found to lower the failure rate in dosage calculation exams with 22 percentage points [96]. However, the flipped classroom approach was found to be more effective when instructors used quizzes at the start of each in-class session [95].…”
Section: Pedagogical Strategies Related To Pathology Teachingmentioning
confidence: 99%
“…De fire undervisningoppleggene er utviklet hver for seg, de springer ut av forskjellige disiplin-og fagtradisjoner, og de har forskjellige fagdidaktiske og forskningsmetodiske tilnaerminger. I tillegg er undervisningen tematisk forskjellig: «flipped classroom»-undervisning i legemiddelregning (Tørris, 2020), en digital laeringsressurs i epilepsi og helseveiledning (Erichsen & Høium, 2021a), en teknologistøttet refleksjonsmodell for studenter i praksis (Urstad et al, 2018) og «Student-Best», et teknologistøttet tverrprofesjonelt samhandlings-og kommunikasjonskurs (Jakobsen et al, 2018).…”
Section: Innledningunclassified
“…Bakgrunn I en kvasieksperimentell studie ble laeringsutbyttet ved «flipped classroom» (FC) og tradisjonell undervisning undersøkt i tilknytning til undervisning i legemiddelregning (Tørris, 2020). Her presenteres noen sentrale elementer fra undervisningen, datagrunnlaget og resultater fra studien.…”
Section: Case 1: «Flipped Classroom»-undervisning I Legemiddelregningunclassified